ADUBAÇÃO NITROGENADA E POTÁSSICA NA CULTURA DO MILHO EM SISTEMA PLANTIO DIRETO DE LONGA DURAÇÃO - Fornari, Allison José (2014)
Nitrogen (N) and potassium (K) are nutrients required in larger amounts by corn, requiring adequate levels of N and K phases of higher demand culture. This study aimed to evaluate the effects of fertilization with N and K nutrition, performance and productivity of maize in long-term tillage system. The experiment was carried out on a Yellow Red Oxisol dystrophic with 530 g kg-1 clay under no-till for 30 years. The sequence of crops adopted before the establishment of the experiment was oat/corn/wheat/soybean/wheat/soybean with the annual crop of oat/corn in 33% of the area and wheat/soybean in 67% of the area. A randomized complete block design was used, with three replications in a split-plot arrangement. The treatments consisted of applications of urea at 0, 75, 150, and 225 kg N ha-1 to subplots within plots with KCl previously at 0, 100, 200, and 300 kg K ha-1. The K rates were applied on the surface before seeding, and the N rates were applied in top dressing when corn plants were at the V4 stage (four fully expanded leaves). The Ca/K, Ca + Mg/K, and √ relationships in the topsoil (0-0.20 m) were linearly reduced with increasing rates of K applied pre-sowing. There was no significant effect of increasing K rates on concentrations of N, P, K, Ca, Mg, S, Mn, Zn, Cu and Fe in corn leaves, dry weight of shoots and grains of corn. The increase in N rates increased the contents of N, P, K, Ca, Mg, S, Mn and Zn in the leaves of corn at the silking stage, increased the concentration of N and decreased the content of P, K, Mn, Zn, and Fe in the aboveground part and increased the concentrations of N, P, K, S, Mn, Zn, and Fe in corn grains. The increasing rates of K increased the extraction of K, while the N rates increased the extraction of N, P, K, Ca, Mg, S, Mn, Zn, and Cu by corn shoots. The export of N, P, K, Ca, Mg, S, Mn, Zn, Cu, and Fe was not affected by K rates, but increased with increasing rates of N applied in corn. Potassium fertilization increased plant height and ear height. Increasing N rates increased stem diameter, plant height and ear height, the dry matter production of shoots, the number of kernels per row and per spike, spike and the mass of the mass 1000 grains. Potassium rates did not significantly influence corn grain yield, while increasing rates of N reached double the corn yield. The N use efficiency decreased with increasing N rates in corn and has not improved with potassium fertilization. The relative grain yield of corn was closely related to foliar N, P, Mg and S. The relative grain yield of corn had closer relations with the products N × P, N × K, and N × S than with N/P, N/K, and S/N ratio in leaf tissue of corn. The results suggest that the high demand of N by corn grown after oat under no-till does not increase the demand for K fertilization in corn, in soil with sufficient content of exchangeable K in the 0-0.20 m layer.